IMPROVING STUDENTS READING COMPREHENSION OF SHORT FUNCTIONAL TEXT BY USING TEAM-PAIR-SOLO TECHNIQUE - Yulianto, Gimin; Bunau, Eusabinus; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The purpose of conducting this research was to improve students reading comprehension of short functional text by using Team-Pair-Solo Technique at SMP PGRI 4 Pontianak in Academic Year 2011/2012. Team-Pair-Solo Technique is one of cooperative learning strategies where the students work together in small group, pair and individual. This classroom action research was intended to solve the problems that occurred in the class, which was students difficulty in comprehending a functional text involving main idea, supporting details, vocabulary and reference. The subject of this research was the eighth grade students of SMP PGRI 4 Pontianak class A which consisted of 32 students. This research was done in two cycles. To collect the data, the researcher used written test, observation checklist tables, and field notes. Key words: Team-Pair-Solo Technique, cooperative learning. Abstrak Tujuan dari dilakukannya penelitian ini adalah untuk meningkatkan pemahaman membaca siswa terhadap teks fungsional pendek melalui teknik Team-Pair-Solo pada SMP PGRI 4 Pontianak tahun pelajaran 2011/2013. Teknik Team-Pair-Solo merupakan salah satu strategi dalam pembelajaran kooperatif dimana para siswa bekerja bersama-sama dalam sebuah kelompok kecil, berpasangan dan secara individu. Penelitian Tindakan Kelas ini dimaksudkan untuk mengatasi masalah yang terjadi di dalam kelas, yaitu kesulitan siswa dalam memahami teks fungsional pendek yang meliputi ide pokok, hal-hal pedukung, perbendaharaan kata, dan kata rujukan. Subyek dari penelitian ini adalah siswa-siswa PGRI 4 Pontianak kelas 8 (delapan) A yang berjumlah 32 siswa. Penelitian ini dilakukan dalam dua siklus. Dalam pengumpulan data, peneliti menggunakan tes tertulis, tabel observasi, dan catatan lapangan. Kata kunci: Teknik Team-Pair-Solo, pembelajaran kooperatif.